Tapping into the Power Lines of Project Success: The Strategic Role of Ethical Climate - Ngoma, Muhammad; Nangoli, Sudi; Kusemererwa, Christopher; Bashir, Hassan; Sekakubo, Johnbosco; Ntayi, Joseph M. (European Journal of Business and Management, 2016)
Success has continued to elude many projects world over and hence raised the need to step up measures aimed at reversing this trend. Given the unique nature of particular projects, any efforts to cause project success ought to be targeted at a clearly defined set of projects. This study aimed at investigating the strategic role that the ethical climate components of Egoism, Principle and Benevolence play in enhancing the performance of Poverty Eradication Projects in LDCs, particularly Uganda. Cross sectional and quantitative survey designs were used with a study sample of 323 National Agricultural Advisory Services (NAADS) projects. The results revealed that the ethical climate components of Egoism, Principle and Benevolence positively relate with and predict performance of poverty eradication projects. These findings generate implications and inform particular recommendations on the success of projects in LDCs as this article articulates.
Keywords: Project; Ethical Climate; Poverty; Performance; Strategy